Pembentukan Keterampilan dan Nilai Keagamaan Siswa melalui Pembelajaran Penyelenggaraan Jenazah di Madrasah Aliyah Darul Ulum Kotabaru - Bahrudin; Hilal Solikin (Milenial: Journal for Teachers and Learning, 2025)
The topic of funeral management skills is an integral component of the 2013 Curriculum at the Madrasah Aliyah level, serving to instill religious values and practical Islamic competencies in students. This study aims to analyze the use of learning media and identify both primary and supplementary learning resources employed in the teaching process of these religious skills at Madrasah Aliyah Darul Ulum Kotabaru. This research adopts a qualitative descriptive approach, with data collected through in-depth interviews and documentation studies. The findings reveal that audio-visual media are the most frequently utilized instructional tools, as they combine visual and auditory information, thereby enhancing students’ understanding of the procedures and stages of funeral rites. The primary learning resource used is the 2013 Curriculum textbook, while the supplementary resources include various classical and modern fiqh books such as Fathul Mu’in, Fathul Qarib, Fiqhus Sunnah, and Fiqh Risalah Pelajaran Tangga Ibadah. These sources are employed by teachers to broaden students’ knowledge and deepen their religious understanding. The study concludes that a combination of audio-visual media and diverse learning resources plays a vital role in enhancing the effectiveness of religious skill learning in madrasahs, particularly in developing students’ practical abilities and religious attitudes.